A Development IOT Based Real-Time Weather Monitoring System Using NodeMCU ESP32 and BMP280-DHT11 Sensor - Beni Satria; Rahmaniar, Rahmaniar; M. Erpandi Dalimunthe; M. Iqbal; Berthauli. S (INFOKUM, 2025)
This research aims to develop an Internet of Things (IoT) based weather station using NodeMCU ESP32 microcontroller, BMP280 sensor, and DHT11 sensor. The main problem faced is the lack of weather monitoring system.real timewhich can be accessed remotely to support decision making based on current environmental conditions. To overcome this, this study designed a system that is able to automatically collect temperature, relative humidity, and atmospheric pressure data and transmit it to an online platform via a Wi-Fi connection. The collected data is displayed in graphical form on the application.Blynkto facilitate further analysis. The system testing was conducted for 21 days in Medan City with average air temperature measurements ranging from 29°C to 34°C and relative humidity between 63% and 76%. The preliminary results show that the system has a measurement accuracy of around 95%, with a fast and stable connection to the platformclouddepending on the quality of the internet service provider. This system allows monitoring of weather conditions in real time.real timevia Android or iOS devices, making it easy for users to monitor weather parameters from any location. This research not only proves the implementation of IoT in weather monitoring but also opens up opportunities for further development in environmental monitoring and resource management applications.